KEPUTUSAN PEMBELIAN DAGING AYAM BROILER DAN PRODUK OLAHAN DAGING AYAM BROILER DI PASAR BESAR KOTA WISATA BATU - Suroto, Karunia Setyowati; Murti, Ariani Trisna; Setiaji, Jatmiko (Universitas Tribhuwana Tunggadewi, 2023)
Broiler chicken meat consumption continues to increase per capita/year consumption of broiler chicken meat by the Indonesian people in 2016 was 5.68 kg per capita/year, an increase of 573 grams (11.2%) in 2017. The decision to buy chicken meat can be influenced by several factors such as product, price, place, promotion, and service. This study aims to determine the factors that influence consumers in buying fresh or processed chicken meat in the big market of Batu City. The type of this research is quantitative research. The sampling technique used purposive sampling with a total sample of 110 respondents. Data collection techniques through the dissemination of questionnaires, interviews, and documentation. The data analysis techniques consist of validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis tests. The results showed that the factors that influence consumers' purchasing decisions in buying fresh chicken meat products and processed products in the big market of Batu Tourism City are product, price, and service factors. Then the factor that has a dominant influence on consumers' purchasing decisions on fresh chicken meat products and processed products in the big market of Batu Tourism City is the product factor.